Chemotherapy For Advanced Oral Cancer - N. N. Khanna; A. Khanna; G. C. Pant; B. Sanyal; S. Khanna (Indian Journal of Plastic Surgery)
A combination of three drugs, cyclophosphamide, methotrexate and 5-Fluorouracil was tried in 50 consecutive cases of advanced oral cancer. The overall response rate was 66%, and the incidence of toxicity 18%. The response was better in primary cases as compared to those who had received prior radiotherapy. However the response was shortlived.